Acute and chronic toxicity of sodium sulfate to four freshwater organisms in water‐only exposures. (15th December 2015) - Wang, Ning; Dorman, Rebecca A.; Ingersoll, Christopher G.; Hardesty, Doug K.; Brumbaugh, William G.; Hammer, Edward J.; Bauer, Candice R.; Mount, David R.
Abstract: The acute and chronic toxicity of sulfate (tested as sodium sulfate) was determined in diluted well water (hardness of 100 mg/L and pH 8.2) with a cladoceran ( Ceriodaphnia dubia ; 2‐d and 7‐d exposures), a midge ( Chironomus dilutus ; 4‐d and 41‐d exposures), a unionid mussel (pink mucket, Lampsilis abrupta ; 4‐d and 28‐d exposures), and a fish (fathead minnow, Pimephales promelas ; 4‐d and 34‐d exposures). Among the 4 species, the cladoceran and mussel were acutely more sensitive to sulfate than the midge and fathead minnow, whereas the fathead minnow was chronically more sensitive than the other 3 species. Acute‐to‐chronic ratios ranged from 2.34 to 5.68 for the 3 invertebrates but were as high as 12.69 for the fish. The fathead minnow was highly sensitive to sulfate during the transitional period from embryo development to hatching in the diluted well water, and thus, additional short‐term (7‐ to 14‐d) sulfate toxicity tests were conducted starting with embryonic fathead minnow in test waters with different ionic compositions at a water hardness of 100 mg/L. Increasing chloride in test water from 10 mg Cl/L to 25 mg Cl/L did not influence sulfate toxicity to the fish, whereas increasing potassium in test water from 1 mg K/L to 3 mg K/L substantially reduced the toxicity of sulfate. The results indicate that both acute and chronic sulfate toxicity data, and the influence of potassium on sulfate toxicity to fish embryos, need to be considered when environmental guidance values for sulfate are developed or refined. Environ Toxicol Chem 2016;35:115–127. Published 2015 SETAC. This article is a US Government work and is in the public domain in the United States.